The Cambridge Global Handbook of Financial Infrastructure - (:unkn) unknown; Justus Liebig University Giessen (My University, 2025)
Financial infrastructures are the lifeblood of political economies and are consistently considered critical by governments. They encapsulate socio-technical processes; not merely cables and computer servers, but the relationship of those in finance to these and other physical objects. The Cambridge Global Handbook of Financial Infrastructure consolidates the study of financial infrastructures by bridging political economy, humanities, sociology and science and technology studies. It delves into the core questions of modern finance, from the effect of digitalization on financial functions to the intricate web of global power dynamics. Drawing together interdisciplinary research, it explores the nuances of inclusivity and exclusivity within financial systems, shedding light on historical inequalities and colonial legacies. Including fresh insights, compelling case studies, and conceptual advances, this essential volume offers invaluable perspectives for informing analysis of the past, present, future of finance, and shaping policy debates.
Keywords: ddc:030; ddc:330